Design of Chatbot System for College Website - Pravin Rashinkar, Shivani; Dilip Wanjol, Neha; Nandkumar Rane, Shivani; P. Shinde, Pushkar; A. Talekar, Sopan (International Journal of Computer Sciences and Engineering, 2021)
Most of the time, Students need to visit college administration office to collect various information regarding college such as Tuition fees, Term Schedule, etc. during admission process or as per their daily needs. Hence, to overcome this problem, a chatbot can be designed and developed which can be easily integrated with any college website to provide necessary information regarding college. The goal of AI based chatbot is to make an efficient conversation between human and machine via auditory or textual methods. This project uses Natural language processing to process the user’s query and generate a meaningful response. Based on the information stored in the database, bot itself determines appropriate response of a particular query fired by user. The Chatbot is based on an Artificial Intelligence algorithm, which analyses user’s question and responds with a Naive Bayes’ algorithm. This system will be a Web Application and can reduces work of college administration providing information to students. It also reduces the workload on the staff to answer all the queries of the students.